2021
DOI: 10.1186/s12879-021-06772-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum CA-125 for the diagnosis of pulmonary tuberculosis: a systematic review and meta-analysis

Abstract: Background Pulmonary tuberculosis (PTB) remains the world’s deadliest infectious killer. Serum CA-125 test are useful in the diagnosis of PTB. Although studies on the relation between CA-125 and PTB have been reported, the specificity and sensitivity of serum CA-125 in diagnosing PTB vary widely among different studies. The present study was performed to evaluate the accuracy of CA-125 for the diagnosis of PTB via a meta-analysis of data obtained from previous studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In a 16-article meta-analysis, the ovarian cancer tumor marker CA-125 has shown promise for detection of ATB with a pooled sensitivity of 0.85 (10). This highlights the importance of thinking outside the box, to identify novel biomarkers and the potential of usingbiomarkers associated with other disease conditions to diagnose ATB.…”
Section: Other Potential Markersmentioning
confidence: 99%
“…In a 16-article meta-analysis, the ovarian cancer tumor marker CA-125 has shown promise for detection of ATB with a pooled sensitivity of 0.85 (10). This highlights the importance of thinking outside the box, to identify novel biomarkers and the potential of usingbiomarkers associated with other disease conditions to diagnose ATB.…”
Section: Other Potential Markersmentioning
confidence: 99%
“…Additionally, a recent systematic review and meta-analysis concluded that CA-125 has a potential role for pulmonary tuberculosis diagnosis but further studies should be conducted. 36 The role of CA-125 in extrapulmonary tuberculosis is still relatively uncertain due to lack of large studies. Chen et al compared 23 peritoneal tuberculosis patients and 47 primary peritoneal cancer on clinical characteristics.…”
Section: Extrapulmonary Tuberculosis and Ca-125mentioning
confidence: 99%
“…[38][39][40] This includes pulmonary cancer, breast cancer, pancreatic cancer, and gastrointestinal cancer. 36 Other conditions may include pregnancy, pelvic inflammatory disease, uterine myoma, endometriosis, liver cirrhosis, and heart failure. 40 Patients with benign or malignant pleural effusions can also have elevated CA-125 levels.…”
Section: Extrapulmonary Tuberculosis and Ca-125mentioning
confidence: 99%
“…However, other authors have expressed their concerns regarding the results being biased toward patients with serous effusions. 11 The use of CA-125 in the diagnosis of PTB in the elderly population has been poorly studied. 11 Therefore, we conducted this study to assess the clinical value of CA-125 levels in diagnosing elderly PTB.…”
mentioning
confidence: 99%
“…11 The use of CA-125 in the diagnosis of PTB in the elderly population has been poorly studied. 11 Therefore, we conducted this study to assess the clinical value of CA-125 levels in diagnosing elderly PTB.…”
mentioning
confidence: 99%